Influence of seed rate and fertilizer levels on agro physiological parameters and yield of dual purpose wheat (Triticum aestivum) - HARENDER, HARENDER; HOODA, V S; SODHI, AMIT; KAVITA, KAVITA; KAVINDER, KAVINDER (The Indian Journal of Agricultural Sciences, 2021)
The experiment was conducted at Research Farm of Agronomy, CCS HAU, Hisar during rabi season of the year 2017-18 and 2018-19 to study the influence of seed rate and fertilizer levels on agro-physiological parameters and yield of dual purpose wheat (Triticum aestivum L.). Four treatments, viz. C 306 without cut (M1), C 306 with cut at 60 DAS (M2), WH 1105 without cut (M3), WH 1105 with cut at 60 DAS (M4) in main plot and six seed rate and fertilizer combinations, viz: 100 kg/ha seed rate + 100% RDF (S1), 100 kg/ha seed rate + 115% RDF (S2), 100 kg/ha seed rate + 130% RDF (S3), 125 kg/ha seed rate + 100% RDF (S4), 125 kg/ha seed rate + 115% RDF (S5), 125 kg/ha seed rate + 130% RDF (S6) in subplot with three replications were laid out in split plot design. Results of this study indicate that wheat plant population was not influenced by different cultivars and different dose of fertilizers, but it was significantly affected by seed rate and fertilizer levels. Plant population was significantly higher (55.11/m.r.l.) in wheat sown at 125 kg/ha seed rate with 130% RDF over wheat sown at 100 kg/ha seed rate with either dose of fertilizer during both the years. Significantly higher dry matter accumulation (400.76 g/m.r.l. at harvest), LAI and total tillers were recorded in WH 1105 under without cut management, whereas, significantly taller plants (138.37 cm at harvest) was recorded in C 306 under without cut management. While comparing the seed rate and fertilizer combination treatments, significantly higher dry matter accumulation (308.38 g/m.r.l. at harvest), plant height (114.47 cm at harvest), LAI and total tillers were recorded in wheat sown at 125 kg/ha seed rate with 130% RDF. Significantly higher grain yield (6203 kg/ha) was recorded in WH 1105 under without cut management sown at 125 kg/ha seed rate with 130% RDF over C 306 under either cut management sown at either seed rate with either fertilizer levels during both years, which was statistically at par with WH 1105 sown at 125 kg/ha seed rate with 115% RDF and WH 1105 sown at 100 kg/ha seed rate with 130% RDF.